2021
DOI: 10.21203/rs.3.rs-870829/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Scoping Review Examining the Integration of Exercise Services in Clinical Oncology Settings

Abstract: Background: Addressing questions surrounding the feasibility of embedding exercise service units in clinical oncology settings is imperative for developing a sustainable exercise-oncology clinical pathway. We examined available literature and provided practical recommendations to inform evidence-based practice, policymaking, and further investigations. Methods: Studies that recruited cancer patients, assessed the co-location of exercise services and cancer treatment units and reported findings on service imple… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The research outlined six studies providing data from 30 exercise programs. Issues relating to funding, lack of a detailed implementation plans, and low organizational buy-in were the major barriers to effective service integration, particularly at the health service level (57). A further study by Kennedy, investigating the implementation of exercise into routine cancer care, was hindered by a web of interrelated challenges across all levels of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…The research outlined six studies providing data from 30 exercise programs. Issues relating to funding, lack of a detailed implementation plans, and low organizational buy-in were the major barriers to effective service integration, particularly at the health service level (57). A further study by Kennedy, investigating the implementation of exercise into routine cancer care, was hindered by a web of interrelated challenges across all levels of the healthcare system.…”
Section: Discussionmentioning
confidence: 99%
“…If not, we call them to come and attend to the referred patients" Similarly, oncology professionals in high-resource settings admitted the role of physiotherapists and tend to refer patients with cancer for recruited physiotherapists (18). On the other hand, there is a lack of implementation plans, funding and organizational prioritization to employ physiotherapists in oncology facilities, which has limited the referral of patients for rehabilitation in Africa (19).…”
Section: Availability Of Physiotherapistsmentioning
confidence: 99%
“…Even when exercise programs are available to survivors, a low percentage enroll and participate, with estimates ranging from 10% to 14%. 41 One program in a rural area reported that less than 1% of the eligible survivors participated in the program offered at a regional cancer center. 42 This is likely due in part to a lack of referral to the program and to low patient uptake when referred.…”
Section: Motivating Cancer Survivors To Engage In Exercisementioning
confidence: 99%